2018
DOI: 10.1002/ncp.10054
|View full text |Cite
|
Sign up to set email alerts
|

Improving Growth for Infants ≤1250 Grams Receiving an Exclusive Human Milk Diet

Abstract: Implementation of a standardized feeding protocol including earlier fortification of maternal milk was associated with improved growth for infants receiving human milk feedings. EHM significantly decreased NEC. Earlier fortification had no effect on NEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 26 publications
2
40
0
1
Order By: Relevance
“…This retrospective study found that fortification of human milk feedings with a human milk based fortifier at enteral feeding intakes <60 mL/kg/day compared to intakes of >60 mL/kg/day was associated with greater growth velocities and less negative changes in z-scores for weight and head circumference in infants <1250 g birth weight. Previous studies of infants receiving human milk fortified with human milk based fortifier found improved weight and length gain velocities associated with earlier fortification in a cohort study [ 5 ] as well as a retrospective study [ 4 ], although a randomized controlled study did not find a significant difference in growth velocities for infants fortified at lower versus higher enteral feeding volumes [ 1 ]. Studies of infants fortified at lower feeding volumes whose human milk was fortified with a bovine fortifier have not demonstrated improved growth in a retrospective study [ 7 ] and a randomized trial [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This retrospective study found that fortification of human milk feedings with a human milk based fortifier at enteral feeding intakes <60 mL/kg/day compared to intakes of >60 mL/kg/day was associated with greater growth velocities and less negative changes in z-scores for weight and head circumference in infants <1250 g birth weight. Previous studies of infants receiving human milk fortified with human milk based fortifier found improved weight and length gain velocities associated with earlier fortification in a cohort study [ 5 ] as well as a retrospective study [ 4 ], although a randomized controlled study did not find a significant difference in growth velocities for infants fortified at lower versus higher enteral feeding volumes [ 1 ]. Studies of infants fortified at lower feeding volumes whose human milk was fortified with a bovine fortifier have not demonstrated improved growth in a retrospective study [ 7 ] and a randomized trial [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the bovine diet breast milk was also supplemented with a bovine-based fortifier. However, in some studies that reported growth, there has been decreased weight gain in infants supported with the EHM diet compared to a bovine diet [2,4]. Growth for infants receiving the EHM diet has been improved by fortifying breast milk earlier than the previous practice of fortifying at 100 mL/kg/day of enteral feeding volume [4][5] and by adding additional calories in the form of human milk cream when fortifying at less than or equal to 100 mL/kg/day [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macronutrient content and macronutrient-energy-ratios of HM, HM+HMF and HM+BMF are given in Table 1. Both groups received 6 mg/kg/d iron supplementation (Ferrum Hausman ® [iron-III-polymaltose-complex] or Aktiferrin ® [iron-II-sulfate] [16]) starting on the 15th day of life until discharge. The observation period ended at a gestational age of 37+0 weeks or discharge, whichever came first.…”
Section: Methodsmentioning
confidence: 99%
“…Based on available data, a sample size calculation was only possible for growth velocity from birth up to 37+0 weeks of gestation: 10% was considered as a minimally relevant effect, and a weighted mean of 13.35 and a weighted SD of 2.3 were derived for the HFM group from previous publications [16,26]. Thus, a sample size of 96 patients per group was sufficient to detect this effect with 90% power at a two-sided significance level of 1%.…”
Section: Methodsmentioning
confidence: 99%